Analisis faktor - faktor yang berhubungan dengan kejadian hipotensi pasca spinal anestesi pada pasien Sectio Caesarea - Sumarno; Septian Mixrova Sebayang; Made Suandika (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Hypotension is a common complication following spinal anesthesia in patients undergoing cesarean section and can affect both the mother and the fetus. Purpose: To identify the factors associated with the incidence of hypotension following spinal anesthesia at Hajjah Andi Depu General Hospital in Polewali Mandar. Method: Observational analytical design with a cross-sectional approach. The study sample consisted of 129 patients undergoing cesarean section under spinal anesthesia, selected using purposive sampling. Data were collected through observation and documentation, including age, preload fluid volume, intraoperative bleeding, and incidence of hypotension. Data analysis used the Chi-Square test and Fisher’s Exact Test with a significance level of p<0.05. Results: Hypotension occurred in 67 respondents (51.9%). There was a significant association between age (p<0.001), preload volume (p=0.038), and intraoperative blood loss (p<0.001) and the incidence of hypotension following spinal anesthesia. The risk of hypotension was higher in patients with a preload of <500 ml and intraoperative blood loss of ≥500 ml. Conclusion: Age, preload volume, and intraoperative blood loss were associated with the incidence of post-spinal anesthesia hypotension in patients undergoing cesarean section. Keywords: Cesarean Section; Fluid Preload; Hypotension; Spinal Anesthesia. Pendahuluan: Hipotensi merupakan komplikasi yang sering terjadi setelah spinal anestesi pada pasien Sectio Caesarea dan dapat memengaruhi kondisi ibu maupun janin. Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan kejadian hipotensi pasca spinal anestesi di RSUD Hajjah Andi Depu Polewali Mandar. Metode: Desain analitik observasional dengan pendekatan cross sectional. Sampel penelitian berjumlah 129 pasien Sectio Caesarea dengan spinal anestesi yang dipilih menggunakan purposive sampling. Data dikumpulkan melalui observasi dan dokumentasi meliputi usia, jumlah cairan preload, perdarahan intraoperatif, dan kejadian hipotensi. Analisis data menggunakan uji Chi-Square dan Fisher Exact Test dengan tingkat kemaknaan p<0.05. Hasil: Kejadian hipotensi terjadi pada 67 responden (51.9%). Terdapat hubungan bermakna antara usia (p<0.001), jumlah cairan preload (p=0.038), dan perdarahan intraoperatif (p<0.001) dengan kejadian hipotensi pasca spinal anestesi. Risiko hipotensi lebih tinggi pada pasien dengan preload <500 ml dan perdarahan ≥500 ml. Simpulan: Usia, jumlah cairan preload, dan perdarahan intraoperatif berhubungan dengan kejadian hipotensi pasca spinal anestesi pada pasien Sectio Caesarea. Kata kunci: HipotensI; Preload Cairan; Sectio Caesarea; Spinal Anestesi.